(untitled) (Research, Society and Development, 2021)
Phenomenology as a current of thought and interpretative approach, anchored in the emerging paradigm, has become a possibility of study and analysis of human care production. This review sought to map and examine the scientific productions in the phenomenological approach developed by Nursing in the thematic area of women’s health. Six databases were researched with the following criteria: adult women who received health care in any setting. The searches resulted in 2,813 studies, of which one hundred and thirteen studies were included. Four analytical support theorists, nine themes and 24 sub-themes were identified. The findings show the growing and potential contribution of this theoretical-methodological approach in the production of knowledge in the field of women’s health. They also express how the daily care of nurses, supported by phenomenology, re-cognizes the life world of health care in the dialogue with the women. These findings indicate new practices in health informed/transformed by the concrete existential situation of the human being, as an epistemological perspective that constitutes the emerging paradigm.